2013
DOI: 10.1089/gtmb.2013.0226
|View full text |Cite
|
Sign up to set email alerts
|

Screening Biomarkers of Prostate Cancer by Integrating microRNA and mRNA Microarrays

Abstract: Objective: In this study, we screened microRNA (miRNA) target genes of prostate cancer by integrating miRNA and mRNA expression profiles after target prediction and performed function enrichment analysis for selected candidate genes. Methods: The miRNA expression profile (GSE36802) and mRNA expression profile (GSE36801) were downloaded from the Gene Expression Omnibus database. We processed data and identified the differentially expressed miRNAs and mRNAs with R packages. Verified targets of miRNAs were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 36 publications
(38 reference statements)
1
16
0
Order By: Relevance
“…more aggressive nature of AA PCa), which could be assessed by systematically disrupting reciprocal pairs with mimic/antagomir treatment of population-specific PCa cell lines and testing for a loss (or gain) of oncogenic function. To date, the integrated analysis of miRNA-mRNA pairs has been limited to a handful of PCa studies (32, 33) and none have been related to PCa disparities.…”
Section: Discussionmentioning
confidence: 99%
“…more aggressive nature of AA PCa), which could be assessed by systematically disrupting reciprocal pairs with mimic/antagomir treatment of population-specific PCa cell lines and testing for a loss (or gain) of oncogenic function. To date, the integrated analysis of miRNA-mRNA pairs has been limited to a handful of PCa studies (32, 33) and none have been related to PCa disparities.…”
Section: Discussionmentioning
confidence: 99%
“…The authors underlined the implication of miRNA-648 in PCa progression, predicting 10 target genes, including eight that have not been previously described in PCa. Using a similar procedure, Feng et al [82] found the overexpression of miR-31, proposing this biomarker to distinguish PCa tissues from benign tissues.…”
Section: Functional Enrichment Resources For Mirna Analysismentioning
confidence: 99%
“…Upregulation of "hsa-miR199a" and "hsa-miR-943" [7,19] and downregulation of "hsa-miR-127-3p" [36] are found responsible for melanoma. The investigations by Feng et al [6] and He et al [9] reported that upregulation of "hsa-miR-505" and "hsa-mir181b," respectively, causes prostate cancer by promoting cell proliferation in prostate gland, and our miRNA selection methodology also identified them as the relevant ones. FMIMS also predicted some miRNAs which target cancer-related genes.…”
Section: Discussionmentioning
confidence: 77%